Outcomes of poor peripheral blood stem cell mobilizers with multiple myeloma at the first mobilization: A multicenter retrospective study in Japan. Issue 3 (21st July 2022) - Miyamoto‐Nagai, Yurie; Mimura, Naoya; Tsukada, Nobuhiro; Aotsuka, Nobuyuki; Ri, Masaki; Katsuoka, Yuna; Wakayama, Toshio; Suzuki, Rikio; Harazaki, Yoriko; Matsumoto, Morio; Kumagai, Kyoya; Miyake, Takaaki; et al.
Abstract: Autologous stem cell transplantation (ASCT) remains an important therapeutic strategy for multiple myeloma; however, a proportion of patients fail to mobilize a sufficient number of peripheral blood stem cells (PBSCs) to proceed to ASCT. In the present study, we aimed to clarify the characteristics and outcomes of poor mobilizers. Clinical data on poorly mobilized patients who underwent PBSC harvest for almost 10 years were retrospectively collected from 44 institutions in the Japanese Society of Myeloma (JSM). Poor mobilizers were defined as patients with less than 2 × 10 6 /kg of CD34 + cells harvested at the first mobilization. The proportion of poor mobilization was 15.1%. A sufficient dataset including overall survival (OS) was evaluable in 258 poor mobilizers. Overall, 92 out of 258 (35.7%) poor mobilizers did not subsequently undergo ASCT, mainly due to an insufficient number of PBSCs. Median OS from apheresis was longer for poor mobilizers who underwent ASCT than for those who did not (86.0 vs. 61.9 mon., p = 0.02). OS from the diagnosis of poor mobilizers who underwent ASCT in our cohort was similar to those who underwent ASCT in the JSM database (3y OS rate, 86.8% vs. 85.9%). In this cohort, one‐third of poor mobilizers who did not undergo ASCT had relatively poor survival. In contrast, the OS improved in poor mobilizers who underwent ASCT. However, the OS of extremely poor mobilizers was short irrespective of ASCT.